2021
DOI: 10.1515/jpm-2020-0512
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fetal Doppler parameters in pregnant women with COVID-19 infection: a prospective case-control study

Abstract: Objectives To investigate the effect of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on fetal Doppler parameters. Methods This was a prospective case-control study conducted in Ankara City Hospital with confirmed SARS-CoV-2 infected pregnants between August 1, 2020 and October 1, 2020. There were 54 COVID-19 confirmed pregnant women and 97 age-matched pregnant women as a control group between 28 and 39 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
2
26
1
Order By: Relevance
“…The possible effect of COVID-19 on fetal Doppler parameters was also investigated in current studies [68,69]. No difference was present between healthy pregnant women and those with mild/moderate COVID-19 in terms of fetal Doppler parameters [69]. However, the pulsatility and resistance indices of umbilical and uterine arteries showed a significant increase in pregnant women recovered from COVID-19 compared to the controls [68].…”
Section: Obstetric and Neonatal Complicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…The possible effect of COVID-19 on fetal Doppler parameters was also investigated in current studies [68,69]. No difference was present between healthy pregnant women and those with mild/moderate COVID-19 in terms of fetal Doppler parameters [69]. However, the pulsatility and resistance indices of umbilical and uterine arteries showed a significant increase in pregnant women recovered from COVID-19 compared to the controls [68].…”
Section: Obstetric and Neonatal Complicationsmentioning
confidence: 79%
“…The possible effect of COVID-19 on fetal Doppler parameters was also investigated in current studies [68,69]. No difference was present between healthy pregnant women and those with mild/moderate COVID-19 in terms of fetal Doppler parameters [69].…”
Section: Obstetric and Neonatal Complicationsmentioning
confidence: 80%
“…Fetal Doppler assessment in COVID‐19 patients is reported to be similar to those in healthy patients, although disagreement exists 23–25 . Furthermore, in COVID‐19 pregnant patients, impaired placental function or Doppler abnormalities seem not to be linked with fetal growth restrictions in second half of pregnancy 9 .…”
Section: Discussionmentioning
confidence: 97%
“…Regretfully, the fetal effects of SARS-CoV-2 infection are still uncertain. In our previous study, we found that COVID-19 infection has no negative effect on Doppler parameters in pregnant women (15). However, due to hyper inflammation, hypoxia, and stress-related conditions; fetal thymus size might be reduced in COVID-19 positive pregnancies.…”
Section: Introductionmentioning
confidence: 85%